Teachers as recontextualisers: a case study analysis of outcomes-based assessment policy implementation in two South African schools - Wilmot, Pamela Dianne (Rhodes University, Faculty of Education, Department of Education, 2006)
The research presented in this thesis is a case study analysis of outcomes-based assessment in Grade 9 Human and Social Sciences of Curriculum 2005 in two South African schools. The research consists of two parts: Phase One, 2002 to 2003, was a qualitative case study, interpretive in orientation and using ethnographic techniques, aimed at understanding teachers' responses to curriculum policy and the role of a school-based intervention, located within critically reflexive practice, in supporting change. During this phase, I was a co-participant operating from an insider position. During Phase Two, 2004-2005, I withdrew from the schools and took up an outsider position in order to analyse and theorise the case study. The findings of the interpretive review revealed a fascinating process of change, with some unexpected results that I lacked the theoretical and methodological tools to process. With support from critical friends, I realised that a dynamic and social process of knowledge recontextualisation had taken place, and that the research had moved beyond its initial goals. Not wishing to compromise my integrity as a qualitative researcher, I changed direction and made use of Basil Bernstein's theorising (1990, 1996) to arrive at a suitable vantage point for the analysis. The main contention of this thesis is that the new OBE curriculum framework offers exciting opportunities for teacher participation in curriculum processes. However, if teachers are to maximise these and become agents of change, they need to acquire the rules of recontextualisation and reposition themselves in the recontextualising field. This implies epistemological empowerment, which takes time and mediation but which can be achieved through an approach to teacher professional development located in critically reflexive practice.
Keywords: Competency-based education -- South Africa; Competency-based education -- South Africa -- Case studies; Educational change -- South Africa; Teacher participation in curriculum planning -- South Africa; Teachers -- Training of -- South Africa